Avaliação clínica e cardiológica de crianças e adolescentes para a prática de atividades físicas regulares - Couto, Caroline Eliane [UNESP]; Bonatto, Rossano César [UNESP]; Bonatto, Célia de Paula Pimenta [UNESP]; Iauch, Bianca Giovanna de Almeida [UNESP]; Leite, Victor de Vicente [UNESP]; Silva, Diogo Lineker Marquetto [UNESP]; Silva, Iara Padoim e [UNESP]; Molina, Letícia Correa da Costa [UNESP]; Santiago, Luiza Tavares Carneiro [UNESP]; Freitas, Natália Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The regular practice of physical activities is important to prevent cardiovascular diseases and other chronic diseases in adults that begin in childhood. There for, the combination of physical activities and base cardiovascular diseases predisposes the individual to the risk of sudden death during the physical activities. The necessity of an cardiologic assessment in children and adolescents before they begin sports physical activities regularly is object of controversy on literature. The aim of this study was to diagnose children and adolescents carriers of heart diseases potentially fatal during the practice of sports physical activities and/or with risk factors to the development of chronic adult diseases that begin on childhood. The results of the nutritional assessment showed a high prevalence of overweight and of individuals with fat body distribution associated with the heart disease in adulthood. The clinical exam was not enough to detect of cardiac changes and the electrocardiogram was important to detect cardiac arrhythmias potentially fatal during the practice of sports physical activities, what reinforce the necessity of its inclusion on routine assessment in the pre-participation in children and adolescents.

A prática regular de atividade física é importante para a prevenção de doenças cardiovasculares e outras doenças crônicas do adulto que se iniciam na infância. Entretanto, a combinação de atividade física e doença cardiovascular de base predispõe o indivíduo ao risco de morte súbita durante a atividade física. A necessidade da avaliação cardiológica em crianças e adolescentes antes de iniciarem atividades físicas esportivas regulares é objeto de controvérsia na literatura. O objetivo deste estudo foi diagnosticar crianças e adolescentes portadores de cardiopatias potencialmente fatais durante a prática de atividade física esportiva e/ou com fatores de risco para o desenvolvimento de doenças crônicas do adulto que se iniciam na infância. Os resultados da avaliação nutricional evidenciaram prevalência alta de excesso de peso e de indivíduos com distribuição da gordura corporal associada à doença cardiovascular na vida adulta. O exame clínico não foi suficiente para detecção de alterações cardíacas e o eletrocardiograma (ECG) foi importante na detecção de arritmias cardíacas potencialmente fatais durante a prática de atividades físicas esportivas, o que reforça a necessidade de sua inclusão na rotina de avaliação pré-participação em crianças e adolescentes.
Keywords: Pediatrics; Cardiology; Physical activity; Pediatria; Cardiologia; Atividade física